2014
DOI: 10.1007/978-3-319-11564-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment Using Classic Neuropsychological and Virtual Reality Based Test: A Study in Obsessive-Compulsive Disorder (OCD) and Schizophrenic Patients

Abstract: Assessment of neurocognitive functioning is a critical task in clinical settings. In many disorders, cognitive impairment precedes the onset of behavioral symptoms, and cognitive decline is a major factor contributing to functional disability. The purpose of the current study was to evaluate the executive functions by comparing the evaluations obtained using a neuropsychological battery with the one obtained using the virtual reality version of the Multiple Errands Test (V-MET). The study population included t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The constraints of the proposed system are angle dependency and load dependency. The public o ce RV is not completely representative and thus may increase or decrease the public o ce RV Filippo La Paglia [27] et al have done a Study in Obsessive-Compulsive Disorder (OCD) and Schizophrenic Patients using Psychometric Assessment Using Classic Neuropsychological and Virtual Reality Based Test. The author had discovered that the assessment of neurocognitive functioning could be a crucial task in clinical settings.…”
Section: Santhosh Kumar[18] Et Al Discussed Deep Learning Approach For Emotion Recognition From Human Bodymentioning
confidence: 99%
“…The constraints of the proposed system are angle dependency and load dependency. The public o ce RV is not completely representative and thus may increase or decrease the public o ce RV Filippo La Paglia [27] et al have done a Study in Obsessive-Compulsive Disorder (OCD) and Schizophrenic Patients using Psychometric Assessment Using Classic Neuropsychological and Virtual Reality Based Test. The author had discovered that the assessment of neurocognitive functioning could be a crucial task in clinical settings.…”
Section: Santhosh Kumar[18] Et Al Discussed Deep Learning Approach For Emotion Recognition From Human Bodymentioning
confidence: 99%
“…En el campo más específico de la psicometría, La Paglia et al (2014) comparan los resultados obtenidos con una versión tradicional y otra virtual de la batería de test neuropsicológicos V-MET, encontrando que las dos están correlacionadas. De la misma manera, Shiban et al (2016) comparan las versiones tradicional y virtual del TSST, encontrando que la realidad virtual podría servir como una herramienta estandarizada para la inducción de estrés en condiciones experimentales.…”
Section: Trabajos Relacionadosunclassified
“…The literature review revealed that virtual reality environments have been used in several areas including medicine (Crochet et al, 2011;Botden et al, 2007;Lucas et al, 2008), psychiatry (Wiederhold, & Wiederhold, 2005;Kim et al, 2008;La Paglia et al, 2014), and engineering (Manseur, 2005;Hilfert & König, 2016). It has been observed that there have been several educational studies in fields such as foreign language (Alfadil, 2017;Legault et al, 2019;Chien, Hwang & Jong,2020), science (Civelek et al, 2014;Sarıoğlu & Girgin, 2020), and STEM (Chen & Huang, 2019;Lund & Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%